2013
DOI: 10.1152/japplphysiol.00778.2013
|View full text |Cite
|
Sign up to set email alerts
|

Fiber atrophy, oxidative stress, and oxidative fiber reduction are the attributes of different phenotypes in chronic obstructive pulmonary disease patients

Abstract: Peripheral muscle dysfunction, associated with reductions in fiber cross-sectional area (CSA) and in type I fibers, is a key outcome in chronic obstructive pulmonary disease (COPD). However, COPD peripheral muscle function and structure show great heterogeneity, overlapping those in sedentary healthy subjects (SHS). While discrepancies in the link between muscle structure and phenotype remain unexplained, we tested whether the fiber CSA and the type I fiber reductions were the attributes of different phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Although many factors are implicated in the respiratory and muscle pathophysiology of COPD, oxidative stress (OS) appears to play a key role [ 4 , 5 ]. The COPD literature usually describes an increase in prooxidants, macromolecular damage (lipid and protein oxidation), and DNA oxidation [ 6 8 ], which correspond to deleterious OS as defined by Jones [ 9 ]. To limit cell damage, a complex antioxidant system may directly scavenge ROS and/or inhibit lipid peroxide reactions [ 10 13 ], but previous studies have shown a decrease in many enzymatic and nonenzymatic antioxidants in COPD patients [ 6 , 7 , 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many factors are implicated in the respiratory and muscle pathophysiology of COPD, oxidative stress (OS) appears to play a key role [ 4 , 5 ]. The COPD literature usually describes an increase in prooxidants, macromolecular damage (lipid and protein oxidation), and DNA oxidation [ 6 8 ], which correspond to deleterious OS as defined by Jones [ 9 ]. To limit cell damage, a complex antioxidant system may directly scavenge ROS and/or inhibit lipid peroxide reactions [ 10 13 ], but previous studies have shown a decrease in many enzymatic and nonenzymatic antioxidants in COPD patients [ 6 , 7 , 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies among studies may be due to the differences in centers and the low number of COPD patients included in the investigations. The literature has also described great heterogeneity from one COPD patient to another suggesting different systemic OS marker profiles, but none of these earlier studies has tested this hypothesis [ 5 8 , 14 ]. The impact of such clinical factors as physical inactivity, tobacco consumption, gender, or nutritional intake on prooxidants and antioxidant levels may explain the individual differences in systemic OS markers among COPD patients but the literature remains unclear [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber type shift is particularly pronounced in COPD; for instance, while chronic sedentary subjects exhibit a one-third lower type I fiber proportion compared to active age-matched counterparts (Proctor et al, 1995;Houmard et al, 1998), a two-third smaller proportion is not unfrequently observed in patients (Couillard and Prefaut, 2005). Muscle fiber type shift appears heterogeneous across COPD as two phenotypes of patients showing different muscle histology (type I fiber proportion) have been identified (Gouzi et al, 2013a). Advanced muscle fiber type shift was characterized by an elevated muscle oxidative stress in particular.…”
Section: Muscle Fiber Typingmentioning
confidence: 99%
“…Compared with patients with COPD and normal lung volumes, those with resting hyperinflation have higher baseline dyspnoea [36,65,66] and significant intolerance to exercise [45]. Albuquerque et al studied a cohort of patients with COPD and described how resting IC/TLC was the best predictor of a low peak oxygen uptake (VO2) during incremental cardiopulmonary testing, with a cut-off value of 0.28 having a sensitivity and specificity of 80.0 % and 89.6 % in identifying patients with a peakVO2 of less than 60 % predicted [67].…”
Section: Characteristics Of the Eh Phenotype: Emphysemamentioning
confidence: 99%